Efficacy of 0.05% Chlorhexidine and 0.05% Cetylpyridinium Chloride Mouthwash to Eliminate Living Bacteria on In Situ Collected Biofilms: An In Vitro Study - Kathrin Becker; Giulia Brunello; Luisa Scotti; Dieter Drescher; Gordon John (MDPI AG, 2021)
Chlorhexidine (CHX) mouthwashes are frequently used as an adjunctive measure for the treatment of periodontitis and peri-implantitis, as well as in patients on maintenance therapy. However, their prolonged use is associated with several side effects. This study aimed at evaluating if a mouthwash with a reduced concentration of CHX combined with cetylpyridnium chloride (CPC) was as effective as a conventional CHX mouthwash in the reduction in living cells in oral biofilms attached to hydroxyapatite (HA) and micro-rough titanium (Ti) surfaces. Four healthy volunteers wore a customized acrylic appliance containing HA and Ti discs for in situ plaque accumulation. Biofilms were grown on the discs for 24 or 48 h and then randomly exposed for 60 s to: 0.05% CHX + 0.05% CPC, 0.1% CHX (positive control) or sterile saline (negative control). Viability assay and live-dead staining were performed to quantify bacterial viability and to distinguish live and dead cells, respectively. At both time points, contrary to saline, CHX, both alone and in combination with CPC, exhibited high antibacterial properties and induced a significant reduction in biofilm viability. This study demonstrates the potential of mouthwashes containing a low concentration of CHX combined with CPC as effective antibacterial agents for long-term applications with reduced undesired side effects.